Hubungan Praktik Cuci Tangan, Kriteria Pemilihan Warung Makan Langganan dan Sanitasi Warung dengan Kejadian Diare pada Mahasiswa Universitas Negeri Semarang - Trikora, Endang; Siwiendrayanti, Arum (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2015)
Diarrhea is an endemic disease in Indonesia and also can cause Extraordinary Occurance (KLB) which often lead to death. This study has a purpose to determine the relationship of hand-washing practices, food stall choosing criteria and sanitation of food stall with diarrhea on students of Semarang State University. This research was an analytical observational study with cross-sectional design. The population in this study were 28,827 active students of the Semarang State University. The samples were 320 students. The instruments were questionnaire and check list. Data analysis was performed using univariate and bivariate (chi square test with α = 0.05). The results of this study were variables related to the incidence of diarrhea in students of Semarang State University were food stall choosing criteria (p = 0.028), and there was no relationship between students hand washing practices (p = 0,705), sanitation of food stall (p = 0,978) with the incidence of diarrhea in students of Semarang State University. The suggestion can be given to UNNES health care centerand medical center were giving health education about good criteria to choose food stall for student. Moreover, medical center can educate the owner of food stall to improve sanitation by the conseling